Pre-normative research in the food sector. (Brussels : Federal Science Policy Brussels, 2002)
Samenvatting:The scientific support programme for pre- normative research in the foodsector andwithin the sustainable development concept aims to put forward evaluationtools thatallow the definition of political orientation in the fields of quality oflife (consumerprotection) and the optimal use of resources (environmental protection).
Keywords: Milieubescherming; Voedingsmiddelenindustrie; Voedingsmiddelenonderzoek